Tecklin's pediatric physical therapy - Spearing, Elena McKeogh; Pelletier, Eric S.; Drnach, Mark (Philadelphia : Wolters Kluwer Health, 2022)
"Jan Tecklin's Pediatric Physical Therapy has been in print since 1989 and is used in many Physical Therapy education programs across the United States and abroad. The text is geared towards entry level Physical Therapy students and provides a comprehensive yet relatable overview of some of the most common pediatric physical therapy diagnoses."--
Preceded by Pediatric physical therapy / [edited by] Jan S. Tecklin. Fifth edition. [2015].
Includes bibliographical references and index.
Keywords: Physical therapy for children; Physical therapy; Children; Infants; Physical Therapy Modalities; Child; Infant; Physical Therapy Specialty